Increasingly urban Marabou Storks start breeding four months early in Kampala, Uganda. (8th December 2017) - Pomeroy, Derek; Kibuule, Micheal
Abstract : In recent decades, Marabou Storks Leptoptilos crumeniferus have become common in many urban centres, including Kampala, Uganda, where, as of 2016, they number several thousand birds, with more than 1 200 breeding pairs. Elsewhere in Uganda, the majority of colonies are also in towns and villages. Traditionally, a bird of savannas, breeding in those areas is timed so that the growing young are in the nest during the December to February drier period, when food for scavengers is expected to be more abundant. In southern Uganda, most colonies start each season around November, and this was originally the case in Kampala. However, in recent years, nesting has begun several weeks earlier for the majority of pairs, and up to four months earlier for a smaller group. The main diet of Marabous in Kampala is human refuse, which is available all year round, so in principle they could nest at any time. However, they do not do that. In 'natural' ecosystems, breeding at the 'wrong' time would probably be disadvantageous, resulting in large young in the nest during rainy periods, a time of food scarcity. Thus, within the traditional nesting season, earlier nesters produce more young. It is not yet clear whether the very early nesters in Kampala also produce more young than the main group. Further understanding of this unusual situation will benefit from continued studies in future years.